The Role of the Pharmacist in Animal Health Care: Case Study in Ilala District, Dar es Salaam. Tanzania (The East and Central African Journal of Pharmaceutical Sciences, 2018)
In this cross-sectional study, the role of pharmacists in animal health care, particularly in the distribution of veterinary medicines in community pharmacies in Dar es Salaam was investigated. Using a semi-structured questionnaire a total of 260 pharmacists were interviewed. The study revealed that majority of the pharmacists play a very limited role in the dispensing of veterinary pharmaceutical products. Pharmacists and veterinary practitioners should compliment each other for the betterment of animal health care. The study highlighted the necessity for introducing veterinary pharmacy lectures in the pharmacy undergraduate curriculum in Tanzania. It further recommends that the Pharmacy Council and the Tanzanian Ministry of Health and Social Welfare enforce continuing professional development as a precondition for the renewal of practice licences for all practising pharmacists.
Keywords: Pharmacist; veterinary medicines; veterinary surgeon